Bottomonium physics at Υ(4S, 5S, 6S) energies with the Belle detector. (August 2016) - Tamponi, Umberto
Abstract: The description of quarkonia as pure quark anti-quark bound states has been recently challenged by the observation of charged states in both the charmonium and bottomonium region and large violations of the heavy quark spin symmetry in hadronic transitions. All these effects can be ascribable to non-negligible contributions from the light quark degrees of freedom in the description of both charmonia and bottomonia. We will report the most recent experimental measurements performed by the Belle collaboration in the Y(4S), Y(5S) and Y(6S) regions, including the measurement of the ratio σ[e + e - → bb ̅]/σ[ e + e- → μ + μ - ], the search for neutral states near the B 0 B̅ 0 threshold, the first observation of the transition ϒ(4 S ) → ηhb (l P ) and the study of the η transitions at the ϒ(5 S ) energy. The contribution to the study of the structure of these states coming from the measurement of hadronic transitions will be discussed.